Priests’ communication practice and perception of code mixing in sunday sermons - Erikson Saragih; Jaharianson Saragih (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
A number of studies on code-mixing have been extensively researched in educational communication; but few studies have explored the practice of code-switching in preaching, which is the domain of religious communication. The study aims to describe the practice of code-mixing in delivering sermons by pastors who use traditional language (Simalungun) as a medium of delivery. The study used a descriptive qualitative research approach with a survey research design using the google form platform as a research instrument, involving sixty priests as the study participants, using the Simalungun language as a medium for delivering sermons. The results of this study reveal that the motivation to use code-mixing is very important to clarify and facilitate the delivery and understanding of the content of the sermon. The results of this study also reveal the reasons, the dominant preaching genre using code-mixing, the language used in code-mixing, the problems faced in practicing code-mixing, as well as the congregation's perception of the practice of code-mixing carried out by pastors. The results of this study provide a complete description of the practice and perception of code-mixing in sermons using the Simalungun language. Further researches on the content of preaching in Sunday sermons using different methods of analysis are suggested by the study.